(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى معرفة أكثر معوقات العمل التطوعي لدى عينة من طلبة الصف الأول الثانوي العام بمدارس محافظة دمشق الرسمية، ذلك من خلال الإجابة عن السؤال التالي : 1- ما أكثر معوقات العمل التطوعي لدى عينة من طلبة الصف الأول الثانوي العام بمدارس محافظة دمشق الرسمية؟ كما هدف البحث أيضاً إلى معرفة الفروق بين تقديرات الطلبة حول معوقات انخراطهم في العمل التطوعي تبعاً لمتغيرات (الجنس، والمستوى التعليمي للأب، والمستوى التعلمي للأم) اعتمد البحث المنهج الوصفي التحليلي باستخدام استبانة مكونة من ( 39) عبارة موزعة على ثلاثة مجالات، ووزعت على عينة من طلبة الصف الأول الثانوي العام قوامها (356) طالباً وطالبةً بلغ عدد الذكور(160)، وعدد الإناث (196).وتوصل البحث إلى النتائج التالية: 1- إن أكثر المعوقات التي تمنع طلبة الصف الأول الثانوي العام من الانخراط في العمل التطوعي هي المعوقات الشخصية، ثم المدرسية، وأخيراً المعوقات التنظيمية. 2- وجود فروق بين الذكور والإناث في المعوقات التي تواجه انخراطهم في العمل التطوعي وفقاً لمتغير الجنس وكانت الفروق لصالح الذكور، وبينت النتائج وجود فروق ذات دلالة إحصائية بين متوسطات درجات إجابات طلبة الصف الأول الثانوي العام عن معوقات العمل التطوعي تعزى لمتغيري المستوى التعليمي للأب والمستوى التعليمي للأم حيث أظهرت النتائج أن الطلبة الذين آباؤهم من ذوي التعليم (إعدادي فما دون) يواجهون معوقات في انخراطهم في العمل التطوعي بشكل أكبر من باقي مستويات التعليم الأخرى. This study tried to find out most impediments to voluntary work among a sample of first grade students at general secondary schools in Damascus Province by answering the following question. What obstacles that most hinder voluntary work among a sample of first grade students at general secondary schools in the province of Damascus? The objective of this research is also to know the differences among students’ estimates of the obstacles hindering their engagement in volunteer based on the variables of (sex, educational level of the father, the learning level of the mother). The research used the descriptive analytical method employing a questionnaire consisting of (39) items divided into three areas and circulated to a sample of (356) first grade students at general secondary schools: (160) male and (196) students. Results were as follows: • Most obstacles preventing first grade students of secondary schools from engaging in voluntary work are personal, related to school, and organizational ones. • There were differences between males and females regarding obstacles to engaging in voluntary work in favor of males. Results also showed statistically significant differences among answers of first grade students at general secondary schools attributed to variables related to the educational level of parents. Students whose parents’ education (preparatory or less) faced obstacles to their involvement in voluntary work more than the rest of students whose parents’ levels of education are higher.